Strategi Pemberdayaan Ekonomi Umat dengan Zakat Berdasarkan Fatwa Kontemporer: Pendekatan Maqashid Syariah - Ahdiyat Agus Susila; Muhammad Lathoif Ghozali (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
The economic empowerment of the ummah is one of the key aspects in enhancing social welfare and the prosperity of Muslim communities. Productive zakat serves as a strategic instrument in realizing this empowerment. Contemporary fatwas issued by the Indonesian Council of Ulama (MUI) and the National Sharia Council (DSN-MUI) provide legal legitimacy for utilizing zakat as capital for productive economic activities. However, analyses of these fatwas from the perspective of Maqashid Sharia remain limited, resulting in a suboptimal understanding of the Sharia objectives in managing productive zakat. This study aims to examine strategies for the economic empowerment of the ummah through productive zakat, using contemporary fatwa analysis based on the Maqashid Sharia approach. The research employs a qualitative method with content analysis of MUI/DSN-MUI fatwa documents related to productive zakat. The Maqashid Sharia framework is used to assess the contribution of these fatwas to the economic welfare (maslahah) of zakat beneficiaries (mustahik). The findings show that the fatwas on productive zakat explicitly support the realization of Maqashid Sharia, particularly in the aspects of hifz al-mal, hifz al-nafs, and hifz al-nasl. The resulting empowerment strategies include strengthening Islamic economic literacy, optimizing productive investment of zakat funds, and providing entrepreneurial mentoring for mustahik. This study affirms that the Maqashid Sharia approach reinforces the role of fatwas as adaptive legal instruments capable of generating public benefit in the economic empowerment of the ummah. Keywords: Productive Zakat, Contemporary Fatwas, Economic Empowerment, Maqashid Sharia.